2012
DOI: 10.1093/ije/dys185
|View full text |Cite
|
Sign up to set email alerts
|

Data Resource Profile: United Nations Children's Fund (UNICEF)

Abstract: The United Nations Children’s Fund (UNICEF) plays a leading role in the collection, compilation, analysis and dissemination of data to inform sound policies, legislation and programmes for promoting children’s rights and well-being, and for global monitoring of progress towards the Millennium Development Goals. UNICEF maintains a set of global databases representing nearly 200 countries and covering the areas of child mortality, child health, maternal health, nutrition, immunization, water and sanitation, HIV/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 2 publications
0
26
1
Order By: Relevance
“…These are publicly available, nationally representative cross-sectional surveys with information on women of reproductive age. The three types of survey collect comparable reproductive, maternal, and child health indicators; more details on their design are available elsewhere 12, 13, 14. For Brazil, data were extracted from the 2013 national health survey, also a nationally representative survey that includes some reproductive indicators but is mainly focused on risk factors for chronic diseases 15 .…”
Section: Methodsmentioning
confidence: 99%
“…These are publicly available, nationally representative cross-sectional surveys with information on women of reproductive age. The three types of survey collect comparable reproductive, maternal, and child health indicators; more details on their design are available elsewhere 12, 13, 14. For Brazil, data were extracted from the 2013 national health survey, also a nationally representative survey that includes some reproductive indicators but is mainly focused on risk factors for chronic diseases 15 .…”
Section: Methodsmentioning
confidence: 99%
“…The Demographic and Health Surveys (DHS), a series of nationally representative household surveys conducted in over 85 countries [ 18 ], was the leading source of RMNCH information used in 59 of the 82 selected studies (72%). Further data sources include the Multiple Indicator Cluster Surveys [ 16 ], Performance Monitoring for Action [ 17 ], country-specific health surveys, censuses, and community surveys (main source of information for malaria).…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…While DIC is useful for model selection, it has no direct interpretation and cannot be used to compare different studies. Additionally, several studies reported the achieved coverage within credible intervals [ 24 ] and the correlation between predicted and observed values [ 16 ].…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…doi: 10.1111/jcap.12131 Adolescence is a crucial period in life marking the transition from childhood to adult age. Around 18% of the world's population is in this life stage (Murray & Newby, 2012) characterized by physical, cognitive, and socio-emotional changes that are often perceived as stressful and having potential negative consequences in terms of psychosocial adjustment (Singh, Bassi, Junnarkar, & Negri, 2015). In this period, an adolescent endeavors to gain a place in the social world by drawing up and realizing his/her personal plans and objectives.…”
Section: Informed Consentmentioning
confidence: 99%